2011
DOI: 10.1186/1756-9966-30-23
|View full text |Cite
|
Sign up to set email alerts
|

LgR5 expression and cancer stem cell hypothesis: clue to define the true origin of esophageal adenocarcinomas with and without Barrett's Esophagus?

Abstract: BackgroundInvestigation of the expression of an intestinal stem cell marker in esophageal adenocarcinomas (EAC) with and without Barrett's Esophagus (BE), with respect to a cancer stem cell (CSC) hypothesis.Materials and methodsExpression of a putative intestinal stem cell marker LgR5 was analyzed in esophageal cancer specimen (n = 70: 41 EAC with BE, 19 EAC without BE, and n = 10 esophageal squamous-cell carcinomas, ESCC) and in the adenocarcinoma cell line OE-33. Ki-67 and Cdx-2 were co-labelled with LgR5 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 41 publications
3
33
0
Order By: Relevance
“…In contrast, the clonal selection model of multi-step carcinogenesis implies that a random solitary cell undergoes malignant transformation, accumulates multiple mutations and subsequently acquires a survival advantage, which leads to clonal selection [17,18]. Our results of significant up-regulation of ABCB5 in precursor lesions and down-regulation in OSCC are in concordance to results in other solid tumor entities investigating CSC markers during carcinogenesis in our previous study [19]. However, it is important to note that the two models are not mutually exclusive, as CSCs themselves may undergo clonal evolution, as already shown for leukemia cells [20,21].…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, the clonal selection model of multi-step carcinogenesis implies that a random solitary cell undergoes malignant transformation, accumulates multiple mutations and subsequently acquires a survival advantage, which leads to clonal selection [17,18]. Our results of significant up-regulation of ABCB5 in precursor lesions and down-regulation in OSCC are in concordance to results in other solid tumor entities investigating CSC markers during carcinogenesis in our previous study [19]. However, it is important to note that the two models are not mutually exclusive, as CSCs themselves may undergo clonal evolution, as already shown for leukemia cells [20,21].…”
Section: Discussionsupporting
confidence: 90%
“…In a previous study, LGR5 was found to be expressed in 35 out of 41 (85%) esophageal adenocarcinoma (EAC) tissues with Barrett's esophagus (BE) and in 16 out of 19 (81%) EAC tissues without BE. By contrast, LGR5 was not found to be expressed in esophageal squamous cell carcinoma tissues (25). In another study, RT-quantitative PCR analysis was performed on a panel of representative cancer cell lines derived from various organs, consisting of 11 colon cancer, 5 human hepatocellular carcinoma, 10 ovarian cancer and 11 lung cancer cell lines (26).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have associated this marker with head and neck carcinoma as it has been detected in the oral tissue of mice as well as in the side populations of HNSCC cell lines (Haegebarth and Clevers, 2009;Rahden et al, 2011).…”
Section: Lgr5/gpr49 (G-protein Coupled Receptor 49)mentioning
confidence: 99%
“…Nestin -Found to be over expressed in oral squamospheres and demonstrates simultaneous increased expression of ABCG2 -It shows inter-relationship between PARP-1, CAF-1/p60 -It is up-regulated in metastasizing samples of OSCC, hence depicting a positive correlation with the aggressiveness of oral tumourigenesis Lim et al, 2011;Vincent-Chong et al, 2012 CD29/β1 integrin -CD29 is an integrin unit associated with very late antigen receptors.…”
Section: Shimada Et Al 2009mentioning
confidence: 99%